2014
DOI: 10.1080/01694243.2014.887255
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of polarity-modulated SIS-based hot-melt pressure-sensitive adhesives

Abstract: In order to develop polarity-modulated hot-melt pressure-sensitive adhesives (HMPSAs), epoxidation of styrene-isoprene-styrene (SIS) copolymers, using in situ prepared per-formic acid was studied. The polymers were characterized with Fourier-transform infrared spectroscopy, 1 H nuclear magnetic resonance spectroscopy, differential scanning calorimetry, and contact angle tests. The epoxidation degree linearly increases with the epoxidation time without side reaction at low temperature. The polarity of the polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…These microphases can be targeted with additives such as tackifying resin or diblock copolymer, allowing for the manipulation of the microstructure and adhesive properties. The adhesive polymers discussed in this work are branched copolymers. The use of pendant groups that are distinctly different (chemically or structurally) from the backbone provides another means for achieving novel property combinations. Previously, it was demonstrated that adhesive properties could be finely tuned through changes in low-molecular-weight pendant group compositions. Extending these chains produces long side chains and the possible aggregation of microstructures, as found for linear block copolymers.…”
Section: Introductionmentioning
confidence: 99%
“…These microphases can be targeted with additives such as tackifying resin or diblock copolymer, allowing for the manipulation of the microstructure and adhesive properties. The adhesive polymers discussed in this work are branched copolymers. The use of pendant groups that are distinctly different (chemically or structurally) from the backbone provides another means for achieving novel property combinations. Previously, it was demonstrated that adhesive properties could be finely tuned through changes in low-molecular-weight pendant group compositions. Extending these chains produces long side chains and the possible aggregation of microstructures, as found for linear block copolymers.…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, when the adhesive weight percent was smaller or larger than 25% in this study, the cohesive forces decreased leading to lower holding power. Similarly, rational polarity (0.05-0.1) of the chosen type of solvent is beneficial to maintaining the original structures of the adhesive [11], which helps the polar and non-polar molecules in HMPSA reach equilibrium in order to produce a better holding power performance. Therefore, choosing an intermediate level of adhesive weight percent and a solvent with intermediate level of polarity may produce a higher holding power.…”
Section: Bond Strengthmentioning
confidence: 99%
“…Tests were conducted after solvent drying. Zhao et al [11,12] prepared a series of HMPSA by melt-mixing all components at elevated temperature. The prepared adhesive was discharged from the mixer and coated onto a PET substrate at similarly high temperature.…”
Section: Introductionmentioning
confidence: 99%